THE USE OF AUTHENTIC ASSESSMENT IN ENHANCING STUDENTS’ READING COMPREHENSION IN AN ONLINE LEARNING OF ENGLISH LITERATURE - Laras Anjarsari; R. Bunga Febriani (Universitas Galuh, 2022)
This study aimed at investigating the use of authentic assessment in improving students' reading comprehension in online learning for English Literature courses. This study used a qualitative approach with the type of case study. The research data were online class observations (non-participant observations) and interviews (semi-structured). The participants in this study were selected purposively consisting of lecturers of English education at a university in West Java. The results of class observations showed that lecturer used authentic assessment in online learning for English Literature courses.The lecturer use text-based teaching methods and also some references from journals; and used learning media through WhatsApp groups Zoom Meetings. It showed that the use of authentic assessment can improve students' reading comprehension through evidence of responses to students’ written literary works as a form of presentation task.